Spatial profiling of endoplasmic reticulum stress markers in tumor associated cells predicts patient outcomes in pancreatic cancer - Georgia Porter; Murray D. Norris; Minoti Apte; Angelica M. Merlot (Neoplasia: An International Journal for Oncology Research)
Introduction: The impact of endoplasmic reticulum (ER) stress in tumor-associated cells, such as cancer associated fibroblasts (CAFs), immune cells and endothelial cells, on patient outcomes in clinical specimens have not been examined. For the first time, we characterized the expression and spatial locations of ER stress markers, BiP and CHOP, in tumor-associated cells and assessed their prognostic significance in a panel of pancreatic ductal adenocarcinoma (PDAC) patient samples. Methods: Multiplex immunofluorescence was performed on tumor microarrays and images were analyzed using HALO AI software. Results: BiP and CHOP were upregulated in CAFs and endothelial cells in PDAC sections relative to non-neoplastic pancreas sections. High BiP expression in CAFs and endothelial cells was associated with greater vascular invasion and in immune cells was correlated with increased tumor size. High CHOP expression in immune cells correlated with poor patient survival. CAFs and immune cells were more likely to express BiP or CHOP when located close (< 20 μm) to tumor cells. High expression of CHOP in CAFs close to tumor cells correlated with improved patient survival. Conclusion: For the first time, this study demonstrated that ER stress occurs in CAFs and immune cells predominantly in proximity to tumor cells in PDAC patient tissue. The correlation of high ER stress in immune cells with poor patient survival highlights the importance of the TME and the use of spatial analysis for the identification of novel biomarkers.